The Effect Of Product Quality And Promotion On Customer Purchase Decisions Of Pizza Hut Restaurant In The City Of Tangerang Selatan With Price As Intervening Variable - Suleman, Dede; Saputra, Fendi; Sugiyah, Sugiyah; Aprillia, Aprillia; Martias, Andi; Rohimah, Luthfia; Herawaty, Mety Titin; Rulando, Refindo Pradikta (IJOSMAS, 2022)
This study aims to examine and examine the effect of product quality, promotion and price on purchasing decisions by Pizza Hut customers in South Tangerang City. This research is quantitative where data is obtained by giving Likert scale questionnaires to respondents who bought Pizza Hut products in the last three months in South Tangerang City. The data collection method used purposive sampling. From the questionnaires distributed online using the google form link, of the 96 respondents who filled out, only 94 data were eligible for further processing using the SmartPLS version 3.0 software. The results showed that product quality, promotion and price had a significant effect on purchasing decisions. price is not significant as a mediating variable on the effect of product quality on purchasing decisions, while on the effect of promotion on purchasing decisions, price becomes a significant mediating variable